THE SCIENTIFIC-THEORETICAL BASES OF RESEARCH KONTROLLINGOV OF TECHNOLOGIES IN MANAGEMENT OF THE ORGANIZATIONS OF SMALL AND MEDIUM BUSINESS (on the example of sphere IT) - A. V. Likhachev (Модернизация, инновация, развитие, 2015)
In this article the author opened the main scientific-theoretical and methodological approaches to studying the kontrollingovykh of technologies in management of the organizations of small and medium business (on the example of sphere IT).